Assessment of Intra‐Aortic Counterpulsation in an Animal Model of Heart Failure and Myocardial Ischemia. Issue 3 (31st October 2018) - Wray, Sandra; Lascano, Elena; Negroni, Jorge; Cabrera Fischer, Edmundo
Abstract: The effectiveness of intra‐aortic balloon pumping (IABP) is currently evaluated using indirect indexes. The diastolic pressure augmentation is quantified using the subendocardial viability ratio (SEVR) and the DABAC/SABAC index (areas beneath the aortic pressure–time signals during the diastolic and systolic periods, respectively). The SEVR requires invasive recordings of left ventricular pressure; the DABAC/SABAC index may represent an alternative, since it only requires an aortic pressure signal. Nonetheless, it has never been used in an animal model of counterpulsated heart failure and ischemia‐reperfusion episode. The aims of this work were: (i) to develop an animal model of heart failure, with a myocardial ischemia‐reperfusion episode, treated with IABP during the reperfusion period; (ii) to evaluate the effects of the IABP using the SEVR and DABAC/SABAC indices; and (iii) to assess the relationship between both ratios. Cardiovascular parameters were obtained in anesthetized sheep, in which induced heart failure and ischemia‐reperfusion episodes were monitored with and without IABP 1:2. Systolic and diastolic blood pressure signals were assessed in the aorta and in the left ventricle. Values of cardiac output and left ventricular wall thickness signals were obtained. Induction of ischemia and heart failure determined decreases in SEVR and DABAC/SABAC indices with respect to their basal stage (0.807 ± 0.118 vs. 0.601 ± 0.107, P < 0.05 and 1.062 ± 0.136 vs. 0.902 ± 0.161, P < 0.05, respectively). Counterpulsated animals whose myocardial reperfusion was accompanied by heart failure showed a significant improvement of wall thickening fraction along time ( R 2 = 0.7627, P < 0.001). During counterpulsated heart failure accompanied by myocardial reperfusion, the SEVR was positively correlated with DABAC/SABAC index.